Accounting Information System Design for Revenue and Expenditure Cycles: Family Optic - Agustina Dwi Purnamasari; Indah Melati (Universitas Muhammadiyah Prof. DR HAMKA., 2026)
This study aims to analyze the business processes and design a Microsoft Excel based accounting information system for Family Optic. Currently, transaction recording at Family Optic is conducted manually using handwritten records, resulting in unstructured transaction documentation, limited inventory monitoring, and revenue estimates based on assumptions. To address these issues, this study designs an accounting information system for the revenue and expenditure cycles. This study employs the System Development Life Cycle (SDLC) method and incorporates the threats and controls framework to identify risks and determine appropriate controls for both cycles. The proposed Excel based accounting information system was tested through transaction simulation only. Therefore, scope of this study is limited to system design and simulation based testing. Full implementation and operational use were beyond its scope. The resulting system integrates a chart of accounts, inventory master data, purchase and sales records, cash receipts and cash disbursements records, journals, and income statements. The design system supports more systematic transaction recording, enables perpetual inventory monitoring, and generates more structured financial information to facilitate business decision making.